ANALYSIS OF SATISFACTION OF NATIONAL HEALTH INSURANCE JKN PARTICIPANTS THROUGH QUALITY OF MOBILE SERVICES AND CONFIDENCE MEDIATED BY DECISION TO CHOOSE MOBILE JKN SERVICE ON BPJS KESEHATAN OF PEKANBARU - Fitria Ichsani; Sri Hartono (Dinasti Publisher, 2020)
The purpose of this study is to find out how Analysis of Satisfaction of National Health Insurance JKN Participants through Quality of Mobile Services and Confidence Mediated by Decision to Choose Mobile JKN Service on BPJS Kesehatan of Pekanbaru, by measuring indicators that influence variables service quality, trust, decision and satisfaction. This research applies a descriptive research design using survey methods. Sampling uses certain criteria where the respondent is a health insurance participant as a sampling technique. This study was tested using the structural equation modeling (Lisrel) approach to test the significance of the significance of the overall model and predetermined pathway. The findings show that mobile service quality variables have a positive and significant effect on decisions, trust variables have a positive and significant effect on decisions, decision variables have a positive and significant effect on participant satisfaction, mobile service quality variables have a positive and significant effect on satisfaction and trust variables have a positive and significant effect on participant satisfaction.